What Really Matters: Experiences of Emergency Remote Teaching in University Teaching and Learning During the COVID-19 Pandemic - Erlam, Gwen D.; Garrett, Nick; Gasteiger, Norina; Lau, Kelvin; Hoare, Kath; Agarwal, Shivani; Haxell, Ailsa (Frontiers in Education, 2021)
The COVID-19 pandemic and related lock downs have accelerated the need for online and remote teaching within university settings. However, due to the abrupt nature of the pandemic, many academic staff were not prepared for this forced transition. This study aimed to understand how the pandemic affected academics at a New Zealand university, with regards to their transition to emergency remote teaching. Specifically, it explores the challenges as well as benefits academics experienced during this transition. Recommendations for future online learning are also made. Academic staff (N = 67) at a New Zealand University completed an anonymous online survey. Quantitative data were analyzed statistically using descriptive and inferential statistics, while qualitative data were analyzed thematically. Major challenges experienced included miscommunication from the university, concerns about student access to technology, finding a quiet space to work, lack of digital competence skills, too much screen-time, managing work hours, and work/life balance. Benefits included enhanced flexibility, enhanced teacher creativity, increasing autonomy of learners, and reduced commute time. Looking forward, academic staff desired future teaching to include blended learning and virtual immersion. New strategies of working remotely are being explored to facilitate teaching and learning while catering to the preferences and skills of both educators and students. Our findings honor the considerable agility of academic staff who sought to sustain and enhance excellence in remote education. At an institutional level our findings point to the need for staff to be supported by their institutions as they further refine their work within new-found spaces.